Recommendations on Ambulance Cardiopulmonary Resuscitation in Basic Life Support Systems. (1st October 2013) - Hock Ong, Marcus Eng; Shin, Sang Do; Sung, Soon Swee; Tanaka, Hideharu; Huei-Ming, Matthew; Song, Kyoung Jun; Nishiuchi, Tatsuya; Leong, Benjamin Sieu-Hon; Karim, Sarah Abdul; Lin, Chih-Hao; Ryoo, Hyun Wook; Ryu, Hyun Ho; et al.
Abstract : AbstractAim. Cardiopulmonary resuscitation (CPR) during ambulance transport can be a safety risk for providers and can affect CPR quality. In many Asian countries with basic life support (BLS) systems, patients experiencing out-of-hospital cardiac arrest (OHCA) are routinely transported in ambulances in which CPR is performed. This paper aims to make recommendations on best practices for CPR during ambulance transport in BLS systems.Methods. A panel consisting of 20 experts (including 4 North Americans) in emergency medical services (EMS) and resuscitation science was selected, and met over two days. We performed a literature review and selected 33 candidate issues in five core areas. Using Delphi methodology, the issues were classified into dichotomous (yes/no), multiple choice, and ranking questions. Primary consensus between experts was reached when there was more than 70% agreement. Questions with 60–69% agreement were made more specific and were submitted for a second round of voting.Results. The panel agreed upon 24 consensus statements with more than 70% agreement (2 rounds of voting). The recommendations cover the following: length of time on the scene; advanced airway at the scene; CPR prior to transport; rhythm analysis and defibrillation during transport; prehospital interventions; field termination of resuscitation (TOR); consent for TOR; destination hospital; transport protocol; number of staff members; restraint systems; mechanical CPR; turning off of the engine for rhythm analysis; alternative CPR; and feedback for CPR quality.Conclusion. Recommendations for CPR during ambulance transport were developed using the Delphi method. These recommendations should be validated in clinical settings.